TISSUE GLYCOGEN LEVEL IN DIFFERENT BODY PARTS OF THE GREEN MUSSEL.S, PERNA VIRIDIS EXPOSED TO ZINC CHLORIDES IN SUMMER SEASON - KHAN, A. K.; SHAIKH, A. M.; ANSARI, N. T. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
Green mussels Perna viridis (shell length 80-90 mm) from Bhatye creek, Ratnagiri in summer were exposed to ZnCl, of 0.2 ppm and 0.4 ppm (1/10" LC, and LC50) for 7 days, 7 days laboratory depuration and 7 days field depuration. The glycogen content in 0.2 ppm and 0.4 ppm exposed (7 days) showed increased level in gill, hepatopancreas and adductor muscles while 7 days laboratory depurated 0.2 ppm group of animal showed increase in gill, hepatopancreas adductor muscles and 0.4 ppm group of animal in adductor muscle, gill, hepatopancreas, siphon. The content in 7 days field depurated 0.2 ppm group of animals showed increase in mantle, hepatopancreas, siphon and adductor muscles while 0.4 ppm group of aninial showed increase in hepatopancreas, siphon and adductor muscles. The results of the study are discussed in the light of zinc impact on the tissues of mussels.